STRATEGI MARKETING PUBLIC RELATIONS URBAN REPUBLIC DALAM MEMBANGUN BRAND AWARENESS - Diva Aulia Topan; Gita Widiasanty (Universitas Prof. Dr. Moestopo (Beragama), 2022)
Urban Republic is a newcomer in the field of electronic retail, starting in 2016 Urban Republic is here to meet the needs of urban communities in big cities in Indonesia. The presence of Urban Republic is not widely known by urban people who actively use social media, this is based on the comparison of Urban Republic's Instagram followers with competitors who are far away. This research was conducted based on the background of the problem and the aim was to find out the marketing public relations strategy used by Urban Republic in building brand awareness to balance out competitors in the electronic retail sector and how to communicate Urban Republic's marketing public relations strategy to the audience in building brand awareness. Qualitative research methods and descriptive research types were used, the data were collected through in-depth interviews with selected informants using the purposive sampling technique. The selected research informants were Urban Republic's public relations, Urban Republic area head, and one of Urban Republic's Instagram followers. The results of this study found that Urban Republic is a retail brand that houses many brands, therefore the strategies used by public relations are diverse and flexible so that they can be used on all brands that are shaded. Urban Republic communicates its marketing public relations strategy through soft-selling communications, namely by press releases, press conferences, and launching events from the shaded brands.